Harga, promsi, inovasi produk dan keputusan pembelian produk zaitun series mustika ratu - Husnayetti, Husnayetti; Sunarsih, Siti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to help Mustika Ratu management determine which factors will influence consumer decisions to buy Saries Mustika Ratu products in the DKI Jakarta area. This research data is primary data obtained by distributing questionnaires through Google forms. The analysis used in this research is data quality test, classical assumption test and multiple linear regression test. The results of the research that has been carried out show that the simultaneous influence of the three variables (Price, Promotion, Product innovation) is seen from the F value, the calculated F value is 11.367 > F table 3.08. This shows that the three variables simultaneously have a significant effect on the purchasing decision variable. The coefficient of determination (R2) which is used to measure how much the model's ability to explain the variation of the dependent variable is 0.244 (24.4%) this shows that 24.4% of price, promotion and product innovation variables affect purchasing decisions while the rest is 77, 6% is explained by other variables.